We're going on a bear hunt - Rosen, Michael, 1946-; Oxenbury, Helen (London : Walker Books, 1996)
Brave bear hunters go through grass, a river, mud, and other obstacles before the inevitable encounter with the bear forces a headlong retreat.
1.5
K-3.
K-3
Keywords: Bears -- Juvenile fiction; Hunting -- Juvenile fiction; Bears -- Fiction; Hunting -- Fiction; Bears -- Fiction; Hunting -- Fiction